Synthesis of N-Alkylated and N-Acylated derivatives of girinimbine - Nor, Siti Mariam Mohd; Osman, Fatin Nurul Atiqah; Ahmad, Kartini; Nafiah, Mohd Azlan (Asian Publication Corporation, 2017)
Girinimbine, a carbazole alkaloid has drawn an attention due to its wide range of pharmacological effects such as antiplatelet, antibacterial and anticancer activities. Five new derivatives of girinimbine were successfully semi-synthesized via modification on N-terminal of naturally isolated girinimbine. N-Benzylgirinimbine, N-butylgirinimbine and N-isopentylgirinimbine were obtained from alkylation reaction, whereas, N-butyrylgirinimbine and N-methylbutyrylgirinimbine were obtained from acylation reaction. The structures of synthesized girinimbine derivatives were confirmed by spectroscopic techniques.